Reconsideration of the development of the distal tubule of the human kidney. - Howie, A J (1993)
The human kidney develops from 2 embryonic tissues, the ureteric bud and the metanephric blastema. The site in the adult renal distal tubule corresponding to the junction between these tissues has never been established unequivocally and is usually said to be the union between the collecting duct and the connecting piece, based on microdissection evidence. We have examined kidneys from 21 human fetuses of various ages using an immunohistological method for substances related to the ABO blood group system, various cytokeratins including those detected by the monoclonal antibody PKK2, and Tamm-Horsfall protein. The ureteric bud and connecting piece expressed the type 1 precursor chain of ABO antigens mostly early in gestation, the H antigen of the ABO system mostly later in gestation, and cytokeratins detected by PKK2. The induced nephrons after the S-shaped body stage expressed Tamm-Horsfall protein. In the adult renal tubule, distal from the macula densa, it was already known that there is a sharp junction between the segment expressing Tamm-Horsfall protein and the more distal segment that expresses the H antigen and cytokeratins detected by PKK2. The finding that the ureteric bud and connecting piece express the same antigens as this segment while the S-shaped body eventually expresses Tamm-Horsfall protein is consistent with the concept that (1) the connecting piece arises from the ureteric bud, not the S-shaped body, and (2) the junction of ureteric bud derivatives and metanephric blastema derivatives is on the distal side of the macula densa at the distal end of Tamm-Horsfall staining.